(untitled) (Research, Society and Development, 2019)
This paper presents a mobile application prototype, integrating the smartphone and Arduino, to assist in the geolocation of visually impaired people, which is one of the problems faced by visually impaired people regarding themselves and objects, especially in unfamiliar and closed environments. Finding the way to a room without assistance is almost impossible for a person with a complete absence of sight. The prototype was developed to be applied at the campus of the Federal University of Santa Maria, in the city of FredericoWestphalen –RS, using the dissertation-project methodology.